2009
DOI: 10.1177/1082013209353078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incorporation of Various Food By-products on Some Nutritional Properties of Rice-based Extruded Foods

Abstract: Various food by-products were incorporated into rice grits and submitted to extrusion cooking to produce fortified extruded food products. The blends of various formulations of durum clear flour (8—20%), partially defatted hazelnut flour (PDHF) (5—15%), fruit waste blend (3—7%) and rice grits were extruded using single screw extruder. Response surface methodology was used to evaluate the effects of process variables, namely the feed moisture content (12—18%), barrel temperature (150—175 °C) and screw speed (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…A positive correlation (R 2 =0.796) was found between phenolic content and antioxidant activity of broccoli extrudates. This finding suggests that the antioxidant activity of produced broccoli-enriched snack is due to a great extent to its phenolic content and is in line with observations of Yağci andGöğϋş (2009) andRepoCarrasco-Valencia et al (2001) who reported a high correlation between DPPH and Folin-Ciocalteau assays in rice-based and kiwicha extruded products respectively. In addition, it should be noted that not such a correlation was observed for olive paste extrudates.…”
Section: Antioxidant Activity Of Extrudatessupporting
confidence: 90%
See 2 more Smart Citations
“…A positive correlation (R 2 =0.796) was found between phenolic content and antioxidant activity of broccoli extrudates. This finding suggests that the antioxidant activity of produced broccoli-enriched snack is due to a great extent to its phenolic content and is in line with observations of Yağci andGöğϋş (2009) andRepoCarrasco-Valencia et al (2001) who reported a high correlation between DPPH and Folin-Ciocalteau assays in rice-based and kiwicha extruded products respectively. In addition, it should be noted that not such a correlation was observed for olive paste extrudates.…”
Section: Antioxidant Activity Of Extrudatessupporting
confidence: 90%
“…The higher moisture content presumably promoted phenolic polymerization, which affected extractability of phenols and reduced antioxidant activity (Brennan et al 2011;Pokorný and Schmidt Š 2003). Yağci and Göğϋş (2009) found for extrudates containing orange peel and grape seed by-products (using rice as a base flour) extruded with single screw extruder, ranging feed moisture content from 12 to 18 %, a reduction in phenolic content. A reduction in phenolic content with feed moisture content was also observed for cerealbased extrudates containing carrot powder (Ozer et al 2006).…”
Section: Phenolic Content Of Extrudatesmentioning
confidence: 98%
See 1 more Smart Citation
“…Although little is known about the effect of extrusion cooking on phenolic composition, thermal processing of beans has been reported to cause important changes (Rocha-Guzmán et al 2007a;Anton et al 2008;Yagcı and Gögüs ‚ 2010). Although little is known about the effect of extrusion cooking on phenolic composition, thermal processing of beans has been reported to cause important changes (Rocha-Guzmán et al 2007a;Anton et al 2008;Yagcı and Gögüs ‚ 2010).…”
Section: Resultsmentioning
confidence: 99%
“…There have been studies carried out on improving the nutritional properties of extrudates by addition of fruit by‐products. Fruits blend waste (orange peel, grape seed, and tomato pomace) was extruded with rice grits by Yağcı and Göğüş . The authors reported that starch digestibility decreased with increasing addition of the fruit blend waste.…”
Section: Introductionmentioning
confidence: 99%